Ethical Leadership in Comparative Perspective - Ashath, Mohamed; Insaf, Mohammed; Aroos, Ashker (UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
This article delves into the shared ethical paradigms between Buddhism and Islam, as epitomized by the governance models of King Aśoka and ʿUmar ibn ʿAbd al-ʿAzīz. Both leaders are widely celebrated for their profound commitment to justice, compassion, and inclusivity, which formed the cornerstone of their approaches to nation-building. King Aśoka, guided by the principles of Dhamma, prioritized non-violence, religious tolerance, and public welfare, transforming his empire into a beacon of ethical governance. Similarly, ʿUmar ibn ʿAbd al-ʿAzīz often hailed as the